2017
DOI: 10.1044/2016_aja-16-0063
|View full text |Cite
|
Sign up to set email alerts
|

Service Delivery to Children With Mild Hearing Loss: Current Practice Patterns and Parent Perceptions

Abstract: Purpose This study investigates clinical practice patterns and parent perception of intervention for children with mild hearing loss (HL). Method Ages at and delays between service delivery steps (first diagnostic evaluation, confirmation of HL, hearing aid [HA] fitting, entry into early intervention) were investigated for 113 children with mild HL. Comparisons were made to children with moderate-to-severe HL. Parents of children with mild HL reported r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
2
17
0
1
Order By: Relevance
“…This is in line with international studies e.g. Australian Hearing [7] and with the findings of Walker et al [45] in the US. Whatever the reasons for the late fitting in mild HL (etiological, medical, social, or organisational), there is today ample evidence for the risk of language learning difficulties and academic shortcomings in mild HL [6,18,22].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with international studies e.g. Australian Hearing [7] and with the findings of Walker et al [45] in the US. Whatever the reasons for the late fitting in mild HL (etiological, medical, social, or organisational), there is today ample evidence for the risk of language learning difficulties and academic shortcomings in mild HL [6,18,22].…”
Section: Discussionsupporting
confidence: 93%
“…A broad definition of mild hearing loss was used in the current study (Walker, Spratford, Ambrose, Holte, & Oleson, 2017). CMBHL qualified if they (a) had a fourfrequency (0.5, 1, 2, and 4 kHz) better-ear PTA greater than 20 dB HL and ≤ 45 dB HL with no more than one threshold from 0.25 to 4 kHz greater than 50 dB HL in the better hearing ear or (b) had a high-frequency hearing loss with one or more thresholds greater than 25 dB HL at or above Note.…”
Section: Hearingmentioning
confidence: 99%
“…Another factor noted to be related to delays in the EHDI process was presence of a mild hearing loss. Walker et al (2017) found that children with mild hearing loss were fitted with hearing aids at significantly greater ages than those with more significant degrees of hearing loss. A similar trend was found in this project.…”
Section: Barriers To Meeting 1-3-6mentioning
confidence: 99%
“…Provider-related barriers include limited access to audiologists with pediatric experience, appointment wait times, and delay in diagnosis of hearing loss due to multiple rescreenings and diagnostic tests (Holte et al, 2012;MacNeil, Liu, Stone, & Farrell, 2007;Munoz, Blaiser, & Barwick, 2013). Patientrelated barriers include patient comorbidities, unilateral or mild hearing loss, general health/neonatal intensive care unit (NICU) stay, and presence of otitis media (Coplan, 1987;Dalzell et al, 2000;Harrison & Roush, 1996;Holte et al, 2012;Moeller, Eiten, White, & Shisler, 2006;Walker, Spratford, Ambrose, Holte, & Oleson, 2017). Family-related barriers include family understanding of the importance of follow-up, subjective observation of the child's response to sounds, acceptance of hearing loss, work schedules, and socioeconomic status (Folsom et al, 2000;Holte et al, 2012;MacNeil et al, 2007;Munoz et al, 2013).…”
Section: Challenges To Meeting the Jcih Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation